Towards a sustainable human right to water : supporting vulnerable people and protecting water resources - Misiedjan, Daphina, 1987-; Netherlands Network for Human Rights Research (Cambridge ; Antwerp ; Chicago : Intersentia, 2019)
With the present growing water stress, conflicts can rise between sustainability efforts and meeting the water needs of populations. Both developing and developed countries are struggling with finding sustainable solutions to provide access to water for everyone, especially vulnerable groups. The further development of the human right to water may provide for a legal solution when subjecting this right to sustainability requirements. The focus of this study is to further develop the human right to water in such a manner that it will encompass the sustainable enjoyment of the right by vulnerable groups. To explore the topic, classic legal methods are adopted through desk research. Also an assessment framework will be developed and used in case studies. Meaning that with the use of qualitative research methods such as interviews, the interaction between the concepts (vulnerability, sustainability and the human right to water) will be examined. This will shine light on the requirements needed for the sustainable enjoyment of the human right to water by vulnerable groups.
General introduction -- Water and vulnerable groups : contextualising vulnerability and identifying vulnerable groups in relation to the human right to water -- The human right to water in international human rights law -- Sustainability in the context of water -- Enhancing the human right to water : finding inspiration from the concept of sustainable development -- Ten building blocks for a sustainable human right to water : an integrated method to assess vulnerable groups' sustainable access to water for domestic purposes -- Suriname -- Conclusions.
"Netherlands Network for Human Rights Research"--Cover.
Includes bibliographical references (pages 243-260).
Keywords: Right to water -- Developing countries; Water resources development -- Law and legislation -- Developing countries; Sustainable development -- Law and legislation -- Developing countries; Water security -- Developing countries; Water-supply -- Law and legislation -- Developing countries; Right to water -- Suriname; Water-supply -- Law and legislation; Water resources development -- Law and legislation; Sustainable development -- Law and legislation; Right to water; Water resources development; Water security; Water-supply.; Suriname; Developing countries